Microtubule affinity regulating kinase 4: A promising target in the pathogenesis of atherosclerosis. Issue 1 (21st July 2021) - Qin, Yu‐Sheng; Li, Heng; Wang, Shu‐Zhi; Wang, Zong‐Bao; Tang, Chao‐Ke
Abstract: Microtubule affinity regulating kinase 4 (MARK4), an important member of the serine/threonine kinase family, regulates the phosphorylation of microtubule‐associated proteins and thus modulates microtubule dynamics. In human atherosclerotic lesions, the expression of MARK4 is significantly increased. Recently, accumulating evidence suggests that MARK4 exerts a proatherogenic effect via regulation of lipid metabolism (cholesterol, fatty acid, and triglyceride), inflammation, cell cycle progression and proliferation, insulin signaling, and glucose homeostasis, white adipocyte browning, and oxidative stress. In this review, we summarize the latest findings regarding the role of MARK4 in the pathogenesis of atherosclerosis to provide a rationale for future investigation and therapeutic intervention. Abstract : MARK4 exerts a proatherogenic effect via regulation of lipid metabolism (cholesterol, fatty acid, and triglyceride), inflammation, cell cycle progression and proliferation, insulin signaling and glucose homeostasis, white adipocyte browning, and oxidative stress. We summarize the latest findings regarding the role of MARK4 in the pathogenesis of atherosclerosis to provide a rationale for future investigation and therapeutic intervention.